PENGACAKAN CUPLIKAN SINYAL SUARA SECARA DIGITAL DENGAN MEMPERGUNAKAN SISTEM MIKROPROSESOR 6802 - Siregar, T.P
Time etement scrambling as a time-domain method o6 speech encryption is considerd. Segmentz ofthe incoming speech signal are split into time elements of average phonemes length, which are then shuffled into new sequences, so that the message is encrypted. At the receiver, encoded message is decoded to have the original one. Experiments of time element scrambling has been done digitally using microprocessor system. The hard-ware of Encipher/Decipher consist of microprocessor evaluation system MEK 6802D5 .interface with : A to D converter as input device, D to A converter as output device and two low-pass filter c ircuits. The soft-ware required, consisting of sevenal programs, has been developped in assembly langguage. Experiments show that the effective length of time element is as f ollows. If the scrambling-process is to shuffle the phonemes, the length of time elements is chosen to be the same az the average phoneme's length, that is 100 ms. For least time-delay, the tength of time elementz can be chosen between 100 ms to 40 ms. Some important characteristics of time elementz scrambling method are: the encoded message requires only the normal speech Bw, both speech quality and voice recognition are of a very high degree, the signal is delayed, synchronisation signal must be generated, processing time is limited.